A) ellos les gustan la movida: Towards a New Syntactic Coding of Experiencer as Subject of gustar in 21st Century Spanish - Barrio de la Rosa, Florencio del (2020)
A number of studies about the thematic structure of the psych verb gustar have been published in the first two decades of the 21st century. These publications are symptomatic of the syntactic changes leading to new coding properties of the experiencer of gustar in contemporary Spanish. In this article we approach the reanalysis of the experiencer as canonical subject of gustar and draw attention to this innovative structure, mostly unobserved by recent research. Our analysis is based on data taken from the Corpus del español. We propose interdialectal contact as the main triggering factor. Preliminary results point to infinitive clauses as the basis of reanalysis and Mexican and Caribbean Spanish as the geographical areas of diffusion.